The effect of mechanical and chemical polishing techniques on the surface roughness of denture base acrylic resins - Mohammed Q. Al-Rifaiy (Elsevier, 2010)
Smooth polished surface of dental prostheses is important to prevent bacterial colonization and plaque accumulation. The acrylic base of prosthodontic appliances needs to be adjusted by grinding which often alters the surface of the denture base. It is therefore important to know how different polishing techniques affect surface roughness of acrylic resin. Objective: The aim of this study was to evaluate the effect of mechanical polishing (MP) and chemical polishing (CP) on the surface roughness of heat cured (HC) and auto cured (AC) denture base acrylic resins. Materials and methods: Sixty acrylic resin specimens (30 × 15 × 3 mm) were made for each of the two types of acrylic resins. Thirty HC specimens received mechanical conventional lathe polishing using cone with pumice slurry and soft brush with chalk powder. The other thirty HC specimens received chemical polishing by immersing in methyl-methacrylate monomer heated to 75 °C ± 1 °C for 10 s. The sixty AC specimens received mechanical and chemical polishing in the same manner. Surface roughness was measured using surface analyzing instrument in microns. The data were statistically analyzed by two-way analysis of variance (ANOVA) followed by post hoc Tukey's test (α = 0.05). Results: The surface roughness mean in microns in order of decreasing values were: CP-HC: 1.4132 μm; CP-AC: 1.3494 μm; MP-AC: 0.7364 μm and MP-HC: 0.6333 μm. Two-way ANOVA revealed that the MP-HC was significantly different from CP-HC and CP-AC (P < 0.05). The MP-AC is also significantly different from CP-HC and CP-AC (P < 0.05). There was no significant difference between MP and CP of HC and AC acrylic resin groups. Conclusion: It can be concluded that MP produced significantly smoother surfaces than CP. The surface roughness obtained by MP was not influenced by acrylic resin type where as this was not true for CP. Keywords: Acrylic resin surface roughness, Mechanical polishing, Chemical polishing